2014
DOI: 10.1016/j.addbeh.2013.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Protection Motivation Theory in predicting cigarette smoking among adolescents in China

Abstract: Reducing tobacco use among adolescents in China represents a significant challenge for global tobacco control. Existing behavioral theories developed in the West – such as the Protection Motivation Theory (PMT) – may be useful tools to help tackle this challenge. We examined the relationships between PMT factors and self-reported cigarette smoking behavior and intention among a random sample of vocational high school students (N = 553) in Wuhan, China. Tobacco-related perceptions were assessed using the PMT Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
83
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 44 publications
13
83
2
Order By: Relevance
“…This agrees with a meta-analysis of 65 related studies representing > 20 health issues (22). Increases in constructs such as perceived severity, perceived susceptibility, response efficacy, and self-efficacy simplified adaptive intentions or behaviours (23).…”
Section: Discussionsupporting
confidence: 76%
“…This agrees with a meta-analysis of 65 related studies representing > 20 health issues (22). Increases in constructs such as perceived severity, perceived susceptibility, response efficacy, and self-efficacy simplified adaptive intentions or behaviours (23).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies on smoking adolescents in Asian countries identified that intrapersonal factors associated with adolescent smoking include lower levels of knowledge on the hazards of smoking among adolescents in China (Yan et al, 2014), positive attitudes towards smoking among Iranian adolescents (Nazarzdeh et al, 2013). In Malaysia, Lim et al also found that adolescents with better knowledge on the hazards of smoking and negative attitudes towards smoking were less likely to smoke (Lim et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
“…It is also introduced as an important factor in preventing smoking behavior among adolescents: i.e. higher level of self-efficacy results in lower rates of smoking and lower level of self-efficacy increases rates of smoking behavior (Kear, 2002;Yan et al, 2013). A number of findings have demonstrated that there is a direct negative relationship between self-efficacy and cigarette smoking: i.e.…”
Section: Self-efficacy and Cigarette Smoking Behaviormentioning
confidence: 98%
“…A number of findings have demonstrated that there is a direct negative relationship between self-efficacy and cigarette smoking: i.e. higher level of self-efficacy results in lower rates of smoking and lower level of self-efficacy yields higher rates of smoking behavior (Hiemstra et al, 2011;Yan et al, 2013).…”
Section: Self-efficacy and Cigarette Smoking Behaviormentioning
confidence: 99%
See 1 more Smart Citation